2021
DOI: 10.3390/biom12010045
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously-Produced Hyaluronan and Its Potential to Regulate the Development of Peritoneal Adhesions

Abstract: Formation of peritoneal adhesions (PA) is one of the major complications following intra-abdominal surgery. It is primarily caused by activation of the mesothelial layer and underlying tissues in the peritoneal membrane resulting in the transition of mesothelial cells (MCs) and fibroblasts to a pro-fibrotic phenotype. Pro-fibrotic transition of MCs—mesothelial-to-mesenchymal transition (MMT), and fibroblasts activation to myofibroblasts are interconnected to changes in cellular metabolism and culminate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 106 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…This effect was confirmed, for example, in dermal, cardiac, lung, renal, and liver fibrosis. 21,[29][30][31][32][33] As was reviewed in our previous study, 14 with respect to the peritoneal cavity, there are just a few studies focused on the role of endogenous HA in the regulation of ECM deposition and accompanying processes, most of them concerning the disruption of peritoneal membrane homeostasis during peritoneal dialysis. 50 Raby et al reported that a higher production of HA during peritoneal dialysis contributes to inflammation and fibrosis through the action TLR2 on MCs and the phosphorylation of ERK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect was confirmed, for example, in dermal, cardiac, lung, renal, and liver fibrosis. 21,[29][30][31][32][33] As was reviewed in our previous study, 14 with respect to the peritoneal cavity, there are just a few studies focused on the role of endogenous HA in the regulation of ECM deposition and accompanying processes, most of them concerning the disruption of peritoneal membrane homeostasis during peritoneal dialysis. 50 Raby et al reported that a higher production of HA during peritoneal dialysis contributes to inflammation and fibrosis through the action TLR2 on MCs and the phosphorylation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…There exists evidence that HA can affect the development of fibrosis in different tissues. 14 HA is a nonsulfated glycosaminoglycan synthetized from cytoplasmic UDP-glucuronic acid (UDP-GlcUA) and UDP-N-acetyl-D-glucosamine (UDP-GlcNAc) by three isoforms of hyaluronan synthases (HAS1-3). Functional co-operation and negative feedback mechanisms between these isoenzymes were reported in MCs by Bart 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The article summarises its role on pulmonary innate immunity and discusses the possible adverse effect and how to deal with them. The last review article “Endogenously Produced Hyaluronan and Its Potential to Regulate the Development of Peritoneal Adhesions” [ 10 ] deals with a specific but relatively common complication of intra-abdominal surgery. The authors are describing the role of hyaluronic acid in intra-abdominal healing, explaining on which base the peritoneal adhesions are developing and gives us the key to develop effective strategies against their formation.…”
mentioning
confidence: 99%